2015
DOI: 10.1016/j.nanoen.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of NiCo2S4 nanostructured arrays on carbon fiber paper for high-performance pseudocapacitors

Abstract: A facile hydrothermal method is utilized to produce nanostructured NiCo 2 S 4 arrays on carbon fiber paper with controlled morphologies to study the effect of morphology on their electrochemical performance in supercapacitors. Specifically, NiCo 2 S 4 solid nanofiber, nanotube, and hollow nanoneedle of the same crystalline structure are synthesized by controlling the conditions of the hydrothermal synthesis. Among the three different morphologies studied, the hollow nanoneedle of NiCo 2 S 4 shows the highest c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
136
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 356 publications
(146 citation statements)
references
References 39 publications
8
136
2
Order By: Relevance
“…The same as Co 2p spectrum. As for the S 2p spectrum, the peaks at 161.5 eV and 162.6 eV correspond to the S 2p 3 , which match well with the results of NiCo 2 S 4 in literature [9,11]. Fig.…”
Section: +supporting
confidence: 87%
See 2 more Smart Citations
“…The same as Co 2p spectrum. As for the S 2p spectrum, the peaks at 161.5 eV and 162.6 eV correspond to the S 2p 3 , which match well with the results of NiCo 2 S 4 in literature [9,11]. Fig.…”
Section: +supporting
confidence: 87%
“…3b) exhibits sharp size distribution ranging from 1 to 4 nm and the pore radius centered at 1.9 nm, which is ideal size for ion transports. Besides, the BET surface area can be calculated to be 74.8 m transition to NiSOH, CoSO, CoSOH [11] and [12]. With the increasing scan rate, the anodic peaks shift towards higher potential and the cathodic peaks shift towards lower potential which is induced by greater electric polarization [7].…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig 4a, the nitrogen adsorption-desorption isotherm belongs to Langmuir H4 type isotherm that has an obvious hysteresis loop in the range of 0.6-1 relative pressure, which indicates the mesoporous characteristic of the sample [39]. The BET specific surface area of the sample is calculated to be 57.9 m 2 /g, which is larger than most of the reported values [35,[39][40]42]. The pore size distribution estimated by BJH method mainly distributes in the range of 1~4 nm and centered at 2.5 nm, suggesting its large specific surface area.…”
Section: Resultsmentioning
confidence: 72%
“…Among these extrinsic pseudo-active materials, metal sulfides have recently emerged as a more promising class of active materials owing to an electronic conductivity greater than that of the corresponding metal oxides or hydroxides. 20,22 To further improve the utilization of metal sulfides, various nanostructures have been directly grown on three-dimensional porous current collectors to create high surface areas, short electron-and ion-transport pathways (which are required for high capacitance), 19,[23][24][25][26][27][28] and excellent rate capability and cycle performance. Xiao et al 19 reported on the preparation of highly conductive NiCo 2 S 4 crystalline nanotube arrays grown on carbon fiber papers using a hydrothermal process, thermal treatments and acid etching processes.…”
Section: Introductionmentioning
confidence: 99%